Impact of corporate governance compliance on the financial performance of Malaysian government linked corporation - Ashwini, Jeyakumar (2021)
The purpose of this study is to shed some crucial light on the impact of corporate governance compliance on the financial performance of Malaysian Government Linked Corporation (GLC). The are 20 GLCs also known as G20 companies were introduced under GovernmentTransformation Programme (GTP) in May 2004. This study uses characteristics of board of directors as component of corporate governance compliance. There are five characteristics of board of directors namely board independence, gender diversity, board size, Chief Executive Officer (CEO) duality and tenure of independent director. These variables are denominated as independent variables. Meanwhile, to measure the financial performance of the company,Return on Asset (ROA) and Return on Equity (ROE) were used as accounting measurement and Tobin’s Q was used for market-based measurement. This study was carried out using secondary data for period of six years which is from year 2014 till 2019. Using multiple regression techniques, this study found that CEO duality gave a negative impact towards firms’ performance. Meanwhile, board independence, gender diversity, board size and tenure of independent director on board gave a positive impact. In terms of significant board size and tenure of independent director is not significant towards financial performance, whereas board independence, gender diversity and CEO duality are significant with financial performance.